Effect of Kangoo Jump on Posture Balance and Postural sway of Children with Autism - Paria Nekouei; Vahid Zolaktaf; Ebrahim Sadeghi-Demneh (Sport Sciences and Health Research)
Introduction: Autism Spectrum Disorder (ASD) is among the most common childhood disorders. The current study aimed to investigate the effect of Kangoo Jump (KJ) exercises on dynamic balance and overall postural oscillations in children with ASD.Materials and Methods: This was a quasi-experimental study. Among children with ASD in the Autism Association and Autism Schools in Tehran City, Iran, 20 subjects were selected using screening tests; after assessing the dynamic balance and general postural sway as a pretest, they were randomly divided into two groups of experimental and control. The experimental group performed KJ exercises for 8 weeks; eventually, all individuals were tested for dynamic balance and postural control as a posttest. The obtained data were analyzed using Analysis of Covariance (ANCOVA).Results: This study suggested that performing KJ significantly improved the dynamic balance in children with an ASD disorder. There was a significant difference between the mean scores of the control and experimental groups in the posttest stage in dynamic equilibrium (P<0.001); however, no difference was observed between the study groups in postural control.Conclusion: Using KJ to improve dynamic balance in children with ASD is beneficial. Therefore, these interventions can improve various aspects of development and balance in children with ASDs.